PENGARUH KEPEMIMPINAN TERHADAP MOTIVASI MASYARAKAT DALAM MEMILIH KEPALA DESA (Hargomulyo, Gedangsari, Gunungkidul) - Widodo Widodo (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
Leadership and motivate of vital importance in governance wheel. Especially government mount the countryside or chief of village. " In order to the increasing of leadership and motivate hence ability Tekhnologi is big effort and its execution represent the effort with and is filling each other intergovernmental and Society. Through/passing  education program, development of science tekhmologi and also program the research, non-stoped to governmental push the make-up of ability tekhnologi. Meanwhile corporate world have to play role active in developing, linking and exploiting it in real activity" (President Soeharto, Political Oration of In front/ahead of conference DPR 15 August 1992).Leadership is an activity in group facility to reach the target with. In group facility, a leader have the mission to influence, to pushing, inviting, leading, moving and if require to force the others or group of so that/to be they do/conduct the related/relevant something that with the target attainment withMotivation is an process of somebody activity in the case of leading, guiding, influencing or controlling mind, feeling from behaviour to others of exist in under its observation. So that effective motivation is motivation which can or able to grow, looking after and developing effort and climate which co-operative in organizational life and in the end can improve the performancePlace in Countryside Hargomulyo,. Research Time of during year 2019. This research use the quantitative descriptive method to explain the independent variable influence of X to variable of dependen Y.Leadership of according to answer from responder determining answer A is 48,07% and responder determine the answer of concerning society Motivation to chosen the countryside head of equal to 46,83.